Ecosystem management: Past achievements and future promises - Gomes, Leonardo Augusto de Vasconcelos; Chaparro, Ximena Alejandra Flechas; Facin, Ana Facin Figueiredo [UNESP]; Borini, Felipe Mendes (Elsevier, 2021)
The introduction of supply chain management (SCM) between the 1980s and 1990s represented a breakthrough in the field of management. SCM provides the analytical and theoretical background to design, plan, and manage production activities involving complex chains of firms. Nowadays, both production activities and incremental and radical innovation are organized through complex networks. Innovations, especially radical ones, have unique characteristics related to production flows, which generate new challenges for researchers and managers. In this study, we argue that similar to SCM, ecosystem management (EM) represents a potential breakthrough in the field. However, no general framework exists to address EM. To address this challenge, we perform a systematic literature review by adopting a hybrid approach that combines bibliometric analysis and content analysis. Our findings offer a historical perspective of how EM and the ecosystem concept have evolved over three generations. Building on and reaching beyond current scholarship, we propose a definition of ecosystem as a type of meta-organization. We also identify the goals, scope, and boundaries of EM. Our contributions invite scholars to explore old and new questions related to innovation and management in a novel way.
Keywords: Distributed value creation; Ecosystem management; Innovation ecosystem; New scientific field; Supply chain management